Exploring residential mobility in Chinese cities: An empirical analysis of Guangzhou. (December 2017) - Li, Si-ming; Mao, Sanqin
In this article we aim to extend the literature on residential decisions and relocation in Chinese cities by explicitly incorporating cohort or generation differences in an event-history analysis of residential mobility in the City of Guangzhou over the period 2000–2012, using data from a survey conducted at the end of 2012. The results reveal not only substantially higher mobility propensities for young adults than middle-aged individuals and senior citizens, but significant differential effects of major determinants such as hukou, educational attainment, membership of the Chinese Communist Party and birth of a child and child rearing, on housing consumption and residential relocation across age cohorts. We argue that such differences in mobility behaviour are attributable, to a significant extent, to the vastly different life experiences of and housing opportunities available to different age cohorts.